2013
DOI: 10.1039/c3ob40519b
|View full text |Cite
|
Sign up to set email alerts
|

Dibenzotetraaza[14]annulene–adenine conjugate recognizes complementary poly dT among ss-DNA/ss-RNA sequences

Abstract: First published on the web Xth XXXXXXXXX 200X DOI:Among three novel DBTAA derivatives only DBTAA-propyl-adenine conjugate 1 showed recognition of the consecutive oligo dT sequence by increased affinity and specific induced chirooptical response in comparison to other single stranded RNA and DNA; whereby of particular 10 importance is up until now unique efficient differentiation between dT and rU. At variance, its close analogue DBTAA-hexyl-adenine 2 did not reveal any selectivity among ss-DNA/RNA pointing out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…Changes of the UV–vis spectra in response to temperature increases of up to 95 °C were negligible, and the reproducibility of the UV–vis spectra upon cooling back to 25 °C was excellent. The UV–vis spectra of new compounds ( AP3am , AP5 ) were similar to previously studied analogues [11] (Supporting Information File 1). …”
Section: Resultssupporting
confidence: 68%
See 4 more Smart Citations
“…Changes of the UV–vis spectra in response to temperature increases of up to 95 °C were negligible, and the reproducibility of the UV–vis spectra upon cooling back to 25 °C was excellent. The UV–vis spectra of new compounds ( AP3am , AP5 ) were similar to previously studied analogues [11] (Supporting Information File 1). …”
Section: Resultssupporting
confidence: 68%
“…Previous studies [11] revealed intriguing recognition of single stranded DNA dT sequences by AP3 (but not AP6 , APH ), whereby intercalation of AP3 , AP6 , APH in double stranded ct-DNA was excluded. Here, we studied in more detail the interactions of AP3 , AP6 , APH as well as the novel AP3am and AP5 with a series of synthetic double-stranded polynucleotides.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations